Art (and) Criticism: Hart Crane and David Siqueiros - Piechucka, Alicja (Text Matters: A Journal of Literature, Theory and Culture, 2018)
The article focuses on an analysis of Hart Crane’s essay “Note on the Paintings of David Siqueiros.” One of Crane’s few art-historical texts, the critical piece in question is first of all a tribute to the American poet’s friend, the Mexican painter David Siqueiros. The author of a portrait of Crane, Siqueiros is a major artist, one of the leading figures that marked the history of Mexican painting in the first half of the twentieth century. While it is interesting to delve into the way Crane approaches painting in general and Siqueiros’ oeuvre in particular, an analysis of the essay with which the present article is concerned is also worthwhile for another reason. Like many examples of art criticism—and literary criticism, for that matter—“Note on the Paintings of David Siqueiros” reveals a lot not only about the artist it revolves around, but also about its author, an artist in his own right. In a text written in the last year of his life, Hart Crane therefore voices concerns which have preoccupied him as a poet and which, more importantly, are central to modernist art and literature.